Addressing institutional and community barriers to development and implementation of community-engaged research through competency-based academic and community training - Hallmark, C. Claire; Bohn, Krista; Hallberg, Lance; Croisant, Sharon A. (Frontiers in Public Health, 2023)
Introduction The National Center for Advancing Translational Sciences (NCATS) focuses on reducing barriers to effective translational research that rapidly translates science to clinical and community interventions to improve individual and community health. Community-Engaged Research (CEnR) plays a crucial role in this process by bridging gaps between research and practice. It effectively generates bi-directional knowledge and communication by engaging patients and communities throughout the translation research process. Skills development, however, is critical to enable investigators and communities to establish successful partnerships in research. While there are many independent CEnR education programs nationally, few curricula are mapped to identified domains and competencies. Assessment of current community engagement educational frameworks and competencies We located three comprehensive efforts to identify CEnR domains and competencies that we aligned to inform development of our curriculum, which we then mapped to these competencies. The first, undertaken by the NCATS Joint Workgroup on Researcher Training and Education and Community Capacity Building (JWG) was developed to assess training opportunities for academic researchers and community partners to increase their capacity to meaningfully engage collaborators in translational research. The JWG identified curricula, resources, tools, strategies, and models for innovative training programs and community engagement in all stages of research. It also conducted a gap analysis of deficiencies in available resources. Using Competency Mapping, they developed a framework for curriculum mapping that included eight domains, each with two to five competencies of knowledge, attitudes, and skills. The second aligned community-engaged research competencies with online training resources across the CTSA consortium, while the third was focused on Dissemination and Implementation training. Actionable recommendations Further informed by a conceptual model to advance health equity, we have adapted and integrated these components into a set of modules designed to educate and empower investigators, trainees, students, and community partners to engage in effective CEnR. Discussion This curriculum fills an important gap in our workforce development and helps to meet needs of our community partners. Following program evaluation and validation, we will offer the curriculum for use and further evaluation by other groups interested in using or adapting it for their own programming.